Anion-exchange red perovskite quantum dots with ammonium iodine salts for highly efficient light-emitting devices. Issue 11 (November 2018) - Chiba, Takayuki; Hayashi, Yukihiro; Ebe, Hinako; Hoshi, Keigo; Sato, Jun; Sato, Shugo; Pu, Yong-Jin; Ohisa, Satoru; Kido, Junji
Abstract Perovskite quantum dots have significant potential for light-emitting devices because of their high colour purity and colour tunability in the visible spectrum. Here, we report highly efficient red perovskite quantum dot-based light-emitting devices. The quantum dots were fabricated by anion exchange from pristine CsPbBr3 using halide-anion-containing alkyl ammonium and aryl ammonium salts. Anion-exchange quantum dots based on ammonium iodine salts exhibited a strong redshift from green emission to a deep-red emission at 649 nm as well as higher photoluminescence quantum yields. Furthermore, the quantum dot-based light-emitting device with the alkyl ammonium iodine salt exhibited an external quantum efficiency of 21.3% and high colour purity, with Commission Internationale de l'Eclairage coordinates of (0.72, 0.28), while the light-emitting device with the aryl ammonium iodine salt showed an external quantum efficiency of 14.1%. Finally, the operational stability of the latter was 36 times higher because the surface ligand density of the corresponding quantum dots was lower. Perovskite quantum dots (QDs) are synthesized via an anion-exchange process where CsPbBr3 is used to realize a highly efficient red light-emitting diode (LED). The perovskite QD-based LED exhibits the highest external quantum efficiency of more than 20% compared with perovskite LEDs.